MINIMIZING RISK IN PROCESS SELECTION FOR MORE EFFECTIVE OPERATIONAL MANAGEMENT AT PT. MAYORA INDAH. TBK - Sangkala, Masnawaty (Administraus, 2024)
This study examines the process of minimizing risks in employee selection to improve operational management at PT Mayora Indah Tbk. Established in 1977, PT Mayora Indah Tbk has grown from a local market in Jakarta to a global presence on five continents. This study analyzes the implementation of process selection for more effective operational management at PT Mayora Indah Tbk. Through a qualitative approach, this study examines the challenges, research methods, results, and conclusions of the company's employee selection practices. The findings point to the importance of minimizing risks in employee selection, including the identification of potential risks, the use of appropriate selection methods, and appropriate risk analysis tools. In conclusion, companies must focus on selection strategies that are in accordance with the company's culture and work environment, with an emphasis on developing employees who have abilities and motivation that are in line with industry demands.